Inhibition of calcium uptake via the sarco/endoplasmic reticulum Ca2+-ATPase in a mouse model of Sandhoff disease and prevention by treatment with N-butyldeoxynojirimycin. - Pelled, D; Lloyd-Evans, E; Riebeling, C; Jeyakumar, M; Platt, F; Futerman, A (2003)
Gangliosides are found at high levels in neuronal tissues where they play a variety of important functions. In the gangliosidoses, gangliosides accumulate because of defective activity of the lysosomal proteins responsible for their degradation, usually resulting in a rapidly progressive neurodegenerative disease. However, the molecular mechanism(s) leading from ganglioside accumulation to neurodegeneration is not known. We now examine the effect of ganglioside GM2 accumulation in a mouse model of Sandhoff disease (one of the GM2 gangliosidoses), the Hexb-/- mouse. Microsomes from Hexb-/- mouse brain showed a significant reduction in the rate of Ca2+-uptake via the sarco/endoplasmic reticulum Ca2+-ATPase (SERCA), which was prevented by feeding Hexb-/- mice with N-butyldeoxynojirimycin (NB-DNJ), an inhibitor of glycolipid synthesis that reduces GM2 storage. Changes in SERCA activity were not due to transcriptional regulation but rather because of a decrease in Vmax. Moreover, exogenously added GM2 had a similar effect on SERCA activity. The functional significance of these findings was established by the enhanced sensitivity of neurons cultured from embryonic Hexb-/- mice to cell death induced by thapsigargin, a specific SERCA inhibitor, and by the enhanced sensitivity of Hexb-/- microsomes to calcium-induced calcium release. This study suggests a mechanistic link among GM2 accumulation, reduced SERCA activity, and neuronal cell death, which may be of significance for delineating the neuropathophysiology of Sandhoff disease.